Optimalisasi Promosi Ekowisata Desa Burai dengan Teknologi Perahu Hybrid dan Website - Suprapto, Bhakti Yudho; Dwijayanti, Suci; Juliantina, Ika (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity assists tourism awareness groups Pokdarwis in developing ecotourism through marketing and production to increase income. The methods used in this community service activity are participatory and collaborative by conducting training and demonstrations. The target partners of this activity are Tourism Awareness Groups (Pokdarwis). While the evaluation instrument is a questionnaire used to assess the understanding and satisfaction of partners Pokdarwis with the training and technology provided and semi-structured interviews were conducted with Pokdarwis members and tourists who have used the service. Then, the data analysis technique is quantitative descriptive analysis, used for the results of the questionnaire by displaying percentages to show the level of understanding, satisfaction, and effectiveness of the training. While for interviews and observations, qualitative thematic analysis is used to identify patterns, challenges, and opportunities felt by partners during the program. The results of this community service show that the level of understanding of Pokdarwis is quite good, reaching 82% who understand and are able to fill in content on the website, and are also able to control hybrid boats, participant satisfaction 81% and readiness for independent implementation 74%.